2005
DOI: 10.1002/pros.20200
|View full text |Cite
|
Sign up to set email alerts
|

Unopposed c-MYC expression in benign prostatic epithelium causes a cancer phenotype

Abstract: By using a retroviral infection strategy followed by tissue recombination we have created a model of human prostate cancer that demonstrates that the c-MYC gene is sufficient to induce carcinogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
48
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 72 publications
(70 reference statements)
1
48
0
1
Order By: Relevance
“…8 C-MYC is a DNA-binding protein that belongs to the MYC/MAD/MAX family of basic-helix-loop-helix-zipper (bHLHz) proteins. 9 The C-MYC protein is a transcription factor that regulates a variety of cellular processes including cell growth and proliferation, cell-cycle progression, transcription, differentiation, apoptosis and cellular motility. 10 C-MYC was one of the first oncogenes identified and its overexpression at the RNA and protein levels has subsequently been linked to a wide variety of human cancers.…”
Section: Introductionmentioning
confidence: 99%
“…8 C-MYC is a DNA-binding protein that belongs to the MYC/MAD/MAX family of basic-helix-loop-helix-zipper (bHLHz) proteins. 9 The C-MYC protein is a transcription factor that regulates a variety of cellular processes including cell growth and proliferation, cell-cycle progression, transcription, differentiation, apoptosis and cellular motility. 10 C-MYC was one of the first oncogenes identified and its overexpression at the RNA and protein levels has subsequently been linked to a wide variety of human cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, retrovirally induced overexpression of MYC can transform primary cultures of benign prostate epithelial cells. 21 Nevertheless, because of a lack of suitable antibodies that can be readily applied for cellular and subcellular localization in archival tissues, the phase of prostate cancer development in which MYC protein is expressed in humans is still unclear. It is critical to directly ascertain MYC protein levels because MYC protein levels are tightly regulated by post-transcriptional and post-translational mechanisms, and the presence of MYC mRNA does not necessarily imply the presence of MYC protein.…”
mentioning
confidence: 99%
“…Over-expression of p57 kip2 has been shown to cause cell growth arrest and senescent phenotype in many cell types (Jin et al, 2004;Williams et al, 2005). P57 kip2 has been considered a candidate tumor suppressor gene due to its location in the genome, biochemical activities, and imprinting status (Jin et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been shown that the expression of p57 kip2 is significantly decreased in human prostate cancer (Jin et al, 2008) and the over-expression of p57 kip2 in prostate cancer cells significantly suppressed cell proliferation and reduced invasive ability (Jin et al, 2008). Further, in LNCaP cells, over-expression of p57 kip2 inhibited tumor formation in nude mice and the prostate of p57 kip2 knockout mice developed prostatic intraepithelial neoplasia and adenocarcinoma suggesting that p57 kip2 is an important gene in prostate cancer tumorigenesis, and the p57 kip2 pathway may be a potential target for prostate cancer prevention and therapy, more specifically, during turmeric chemoprevention (Jin et al, 2004(Jin et al, : 2008Williams et al, 2005). The Rad9 gene has many functions that could bear on carcinogenesis, including a role in maintaining genome integrity and regulating cell cycle checkpoints (Lieberman et al, 1996;Bessho & Sancar, 2000;Komatsu et al, 2000;Hopkins et al, 2004;Aiping et al, 2008).…”
Section: Discussionmentioning
confidence: 99%